SiO2-Al2O3-ZrO2-Ag Composite and Its Signal Enhancement Capacity on Raman Spectroscopy - Jesús Alberto Garibay-Alvarado; Pedro Pizá-Ruiz; Armando Erasto Zaragoza-Contreras; Francisco Espinosa-Magaña; Simón Yobanny Reyes-López (Chemosensors)
A ceramic–metal composite was synthesized using sol–gel and electrospinning methods to serve as a SERS substrate. The precursors used were tetraethyl orthosilicate, aluminum nitrate, and zirconium, and polyvinylpyrrolidone was added to electrospun nonwoven fibrous membranes. The membranes were sintered, decorated with silver nanoparticles. The enhancement substrates were made of fibers of cylindric morphology with an average diameter of approximately 190 nm, a smooth surface, and 9 nm spherical particles decorating the surface of the fibers. The enhancement capacity of the substrates was tested using pyridine, methyl orange, methylene blue, crystal violet, and Eriochrome black T at different concentrations with Raman spectroscopy to determine whether the size and complexity of the analyte has an impact on the enhancement capacity. Enhancement factors of 2.53 × 102, 3.06 × 101, 2.97 × 103, 4.66 × 103, and 1.45 × 103 times were obtained for the signal of pyridine, methyl orange, methylene blue, crystal violet, and Eriochrome black T at concentrations of 1 nM.